2018
DOI: 10.1177/1076029617746506
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Generation Biomarkers Decline With Parenteral Anticoagulation—An Overlooked Means of Anticoagulation Monitoring?

Abstract: Anticoagulation therapy is administered to patients to prevent or stop thrombin generation in vivo. Although plasma tests of in vivo thrombin generation have been available for more than 2 decades, they are not routinely used in clinical trials or practice to monitor anticoagulation therapy. We observed a fall in one such marker, the D-dimer antigen, in patients receiving anticoagulation therapy. We therefore conducted a systematic review of the medical literature to document the change in serum biomarkers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
(70 reference statements)
0
1
0
1
Order By: Relevance
“…This is believed to be partly caused by changes in the structure of the resulting fibrin clots [30]. In addition, all thrombin generation markers (F1+2, TAT, and D-dimer) [31] have been reported to be elevated in patients with thrombosis [32]. Indeed, in a cohort of cancer patients (n = 821) it was observed that elevated levels of F1+2 and D-dimer were associated with the occurrence of thromboembolic incidents [33].…”
Section: Discussionmentioning
confidence: 99%
“…This is believed to be partly caused by changes in the structure of the resulting fibrin clots [30]. In addition, all thrombin generation markers (F1+2, TAT, and D-dimer) [31] have been reported to be elevated in patients with thrombosis [32]. Indeed, in a cohort of cancer patients (n = 821) it was observed that elevated levels of F1+2 and D-dimer were associated with the occurrence of thromboembolic incidents [33].…”
Section: Discussionmentioning
confidence: 99%
“…Уровни D-димера позитивно ассоциированы с окисленными фосфолипидами apoB-содержащих липопротеинов, некрозом, эрозией и разрывом каротидной бляшки [69], риском инсульта при острой сердечной недостаточности [18], мерцательной аритмией [136], тромбозом глубоких вен [88], риском венозного тромбоэмболизма у пациентов с злокачественными заболеваниями системы крови [110]. D-димер -показатель генерации тромбина и адекватности антикоагулянтной терапии [87].…”
Section: факторы ангиогенезаunclassified